Back and front peripersonal space: behavioural and EMG evidence of top-down and bottom-up mechanisms - Cocchini, Gianna; Müllensiefen, Daniel; Platania, Ruggero; Niglio, Chiara; Tricomi, Enrica; Veronelli, Laura; Judica, Elda (Experimental brain research, 2024)
Previous studies have identified a ‘defensive graded field’ in the peripersonal front space where potential threatening stimuli induce stronger blink responses, mainly modulated by top-down mechanisms, which include various factors, such as proximity to the body, stimulus valence, and social cues. However, very little is known about the mechanisms responsible for representation of the back space and the possible role of bottom-up information. By means of acoustic stimuli, we evaluated individuals’ representation for front and back space in an ambiguous environment that offered some degree of uncertainty in terms of both distance (close vs. far) and front-back egocentric location of sound sources. We aimed to consider verbal responses about localization of sound sources and EMG data on blink reflex. Results suggested that stimulus distance evaluations were better explained by subjective front-back discrimination, rather than real position. Moreover, blink response data were also better explained by subjective front-back discrimination. Taken together, these findings suggest that the mechanisms that dictate blink response magnitude might also affect sound localization (possible bottom-up mechanism), probably interacting with top-down mechanisms that modulate stimuli location and distance. These findings are interpreted within the defensive peripersonal framework, suggesting a close relationship between bottom-up and top-down mechanisms on spatial representation.